2014
DOI: 10.1590/1519-6984.26712
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbial community in a lotic environment to assess the effect of pollution on nitrifying and potentially pathogenic bacteria

Abstract: This study aimed to investigate microbes involved in the nitrogen cycle and potentially pathogenic bacteria from urban and rural sites of the São Pedro stream. Water samples were collected from two sites. A seasonal survey of bacterial abundance was conducted. The dissolved nutrient content was analysed. PCR and FISH analysis were performed to identify and quantify microbes involved in the nitrogen cycle and potentially pathogenic bacteria. The seasonal survey revealed that the bacterial abundance was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…191-200 197/200 197 surviving for several days on hospital surfaces and are characteristically resistant to antibiotics and sanitizers (Sánchez-Gómez et al, 2015). This results represented a significant found, so the survival and persistence of pathogenic bacteria in natural environments associated the foodborne illness be considered serious public health problem (Medeiros et al, 2014). Konecka-Matyjek et al (2012) reported that food service areas are considered critical to health and, therefore, the microbiological quality of food handling surfaces in hospital kitchens must be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…191-200 197/200 197 surviving for several days on hospital surfaces and are characteristically resistant to antibiotics and sanitizers (Sánchez-Gómez et al, 2015). This results represented a significant found, so the survival and persistence of pathogenic bacteria in natural environments associated the foodborne illness be considered serious public health problem (Medeiros et al, 2014). Konecka-Matyjek et al (2012) reported that food service areas are considered critical to health and, therefore, the microbiological quality of food handling surfaces in hospital kitchens must be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms perform an important role in increasing root growth, germination rate, leaf surface area water and mineral uptake percentages, crop yield and tolerance or resistance to stresses. Nitrifying and denitrifying microbes have great impact on ecosystem that it mediates nitrogen cycle (Medeiros et al, 2014). The most common bacterial genera involved in PGPR are Bacillus, Azospirillum and Burkholderia (Mangmang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…was performed 22 years before our study. Pollution and climate change, including increases in CO 2 , precipitation, temperature, and nitrogen deposition, may influence the presence and activity pattern of both commensal and potentially pathogenic bacteria . These factors have changed over 22 years and may therefore have contributed to the difference in type and prevalence of bacterial isolates identified in the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pollution and climate change, including increases in CO 2 , precipitation, temperature, and nitrogen deposition, may influence the presence and activity pattern of both commensal and potentially pathogenic bacteria. [37][38][39] These factors have changed over 22 years and may therefore have contributed to the difference in type and prevalence of bacterial isolates identified in the two studies. Looking at the factor age, statistical analysis showed that animals harboring viridans streptococci and Moraxella species were significantly younger.…”
Section: Discussionmentioning
confidence: 99%